Sustainable practices of fabric waste among small-scale garment enterprises in the Kumasi metropolis - Ibrahim, Mohammed; Howard, Ebenezer Kofi; Amos, Emmanuel; Fobiri, George Kwame; Schall, Maud; Oppong, Diana (Sustinere: Journal of Environment and Sustainability, 2025)
In recent years, fabric waste has become an important sustainability issue that raises concerns and attracts attention from stakeholders in the fashion industries and the media. Over the past 15 years, the production and consumption of clothing have increased substantially, driven by the rise of demand for fashionable style and the proliferation of fast fashion. This study explores the fabric waste generated by the garment operators within the Kumasi metropolis. A qualitative research design, guided by a phenomenological approach was employed. Data were collected from six zones using purposive sampling technique to select respondents. Interviews and observations served as the primary data collection methods, and data were analysed thematically using NVIVO software. The findings reveal that the use of single-ply and bulk-ply cutting techniques in garments construction led to the generation of tons of fabric waste, particularly among small-scale garment producers. It is recommended that garment operators adopt effective strategies for reusing and responsibly disposing of fabric waste. Furthermore, the use of biodegradable fabrics is encouraged, as they have a lower environmental impact.